Building Resilient Communities Through Earthquake and Tsunami Disaster Education and Mitigation at Aik Belek State Elementary School, Montong Ajan Village, Central Lombok - Syamsuddin, Syamsuddin; Rahmatun Inayah; Ika Umratul Asni Aminy; Nela Ranita Amanda; Ahmad Rifaldi Arahman; Muhammad Ihzan; Siti Azizah; Ziyadatun Adawiyah; Ayu Mona Erisa Marpaung; Kormil Saputra (Future Tecno-Science Publisher, 2025)
Montong Ajan Village is one of the areas in East Lombok Regency that has a high level of vulnerability to earthquakes and tsunamis, considering its location close to the Sumba Megathrust zone. The lack of disaster literacy among the community, especially elementary school children, is a major challenge in disaster mitigation efforts. This community service activity aims to improve disaster mitigation knowledge and skills through an educational and participatory approach. The activity was carried out at Aik Belek State Elementary School (SDN), with methods that included delivering visual materials, group discussions, earthquake evacuation simulations, introducing local risk maps, and practicing preparing disaster preparedness bags. The results of the activity showed an increase in participants' understanding of emergency response steps and high enthusiasm in participating in the simulation. In addition, teachers and schools showed a commitment to integrating disaster education into thematic learning activities. This activity is expected to be the first step towards the formation of a resilient community that is able to respond to disasters quickly, appropriately, and independently.